Causes and Consequences of Cohabitation among Students of Federal Polytechnics Offa, Kwara State, Nigeria - Bello Bolanle Muhinat (Universitas Muhammadiyah Makassar, 2022)
The culture of chastity and purity is no longer promoted and encouraged among the youths, especially those who are out for school in tertiary institutions. This study, therefore, investigated the Causes and Consequences of Cohabitation among Students of Federal Polytechnic Offa, Kwara State, Nigeria. A descriptive survey was adopted for the study where 200 students from 0ND2 and HND2 were purposively chosen and then selected at random. A researcher designed a questionnaire in a Likert scale of Strongly Agree, Agree, Disagree and Strongly Disagree containing 16 items but divided into two halves into causes and consequences of cohabitation was the instrument used for the collection of data. The data was validated via experts and the test-retest method was used to arrive at a reliability index of 0.69. The data was analysed using descriptive statistics. Mean ratings of simple percentages were used to answer the research questions. Causes of cohabitation were seen to include among others insufficient on-campus accommodation, financial distress, fear of losing loved ones, moral and religious decadence while death, STDs, drop out of school poor academic performance and health or social issues were seen as some of the consequences of cohabitation. It was recommended among others that the school authority should try to provide sufficient on-campus accommodation for the students.